(untitled) (The South East European Journal of Economics and Business, 2026)
This study examines the interplay of financial self-efficacy, financial behavior, financial satisfaction, and life satisfaction of young individuals using Psychological Capital Theory (PCT). Analyzing data from 970 high school and university students in Croatia using structural equation modeling, we find that higher financial self-efficacy positively influences financial behavior. Additionally, responsible financial behavior significantly enhances financial satisfaction, which in turn boosts life satisfaction. Our results indicate a partial mediation effect of financial satisfaction between financial self-efficacy and life satisfaction. The study suggests incorporating behavioral interventions in financial education programs to increase self-efficacy and financial capability perceptions among youth. These interventions have the potential to improve financial behavior and overall happiness among young individuals. These insights are valuable for educational policymakers, financial advisors, planners, psychologists, and behavioral researchers. Effective financial education programs can thus contribute to enhancing youth satisfaction by focusing on increasing financial self-efficacy and responsible financial behavior.